CO2 capture by task specific ionic liquids (TSILs) and polymerized ionic liquids (PILs and AAPILs) - Raja Shahrom, M.S. (Elsevier B.V., 2016)
In the present study, new ionic liquids (ILs) such as task specific ionic liquids (TSILs), polymerized ionic liquids (PILs), and amino acid-based polymerized ionic liquids (AAPILs) were synthesized and their efficiency for capturing CO2 was studied. Nitrile imidazolium-based TSILs with different alkyl chain length and different anion (DDS, TFMS, SBA, BS, DOSS), PILs consisting of VBTMA, VBTEA and METMA cations and BF4,Cl, NO3, PF6 and TFMS anions and AAPILs incorporating VBTMA as cation and Arg, Pro as anions were synthesized. The results showed that the CO2 sorption increases as alkyl chain length increased and C2CNDimDOSS gave the highest CO2 sorption among the TSILs, which reach up to 0.55 mol fraction at 10 bar, 298 K. In polymerized ionic liquids the CO2 sorption capacity increases in polymeric forms than monomeric forms. To enhance the efficiency of PILs for adsorbing CO2, AAPILs have been studied. The results showed that the AAPILs are capable of capturing CO2 more than TSILs and PILs as they have functionalized amine tethered at the anion. The result of CO2 sorption showed that even at low pressure (Peq 0.7 bar) and 298 K, the AAPILs VBTMAArg and VBTMAPro absorbed 0.530 and 0.38 mol fractions of CO2. Â© 2016 Elsevier B.V. All rights reserved.